Evaluation of Ice, Cloud, And Land Elevation Satellite-2 (ICESat-2) land ice surface heights using Airborne Topographic Mapper (ATM) data in Antarctica. Issue 7 (3rd April 2021) - Shen, Xiaoyi; Ke, Chang-Qing; Yu, Xuening; Cai, Yu; Fan, Yubin
ABSTRACT: The land ice surface heights derived from Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2) were assessed by comparing to the near-coincident measurements from the Airborne Topographic Mapper (ATM) Light Detection and Ranging (LiDAR) system during the 2018 Operation IceBridge mission in Antarctica. Over the marginal and interior Antarctic Ice Sheet, the ICESat-2 ice surface height was accurate to less than 14 cm, and remarkable correlations ( R 2 = 1) were found through the comparison to the ATM measurements. Centimetre-scale accuracy was seen for all ICESat-2 beams, ranging from −13 cm to −3 cm. The ICESat-2 land ice surface height performance was affected by the terrain conditions (i.e., surface roughness and slope); larger height differences could be seen when the surface roughness or slope values were higher as it becomes difficult for photons to accurately capture height distributions in areas with complex measurement geometry. No evident performance difference was found for the ICESat-2 beams; weak beams can still be used for height measurement. The fine spatial resolution and centimetre-scale accuracy of the ICESat-2 land ice elevation product make it one of the most suitable data sources for ice surface height measurements.